The Effect of Firm Size, Listing Age, and Auditor Reputation on Internet Financial Reporting - Dini Wahjoe Hapsari; Yeni Jelita Jelita (International Journal of Economics Development Research (IJEDR), 2023)
The Monetary Associations Authority arranges clearly recorded relationship to have a site with cash related and non-monetary execution information. The component of cash related and non-monetary data on the affiliation's site is a portrayal of online monetary determining, in fact. The objective of this study was to take a gander at the concurrent and fractional impacts of business size, posting age, and supervisor notoriety on web cash related revealing. The amount of tenants in this examination contains framework locale tries that were recorded on the Indonesia Stock Trade some spot the extent of 2017 and 2021. Purposive taking a gander at was utilized as an outline framework in this review. During the five-year center around period, the model aggregated a measure of 195 bits of knowledge from 39 model affiliations. This study utilized a quantitative evaluation method. To assess the information in this study, specific unquestionable tests and board information lose the faith tests were utilized. Eviews programming adaptation 12 will be used in managing the amassed information. As shown by the review's exposures, business size, posting age, and examiner notoriety all impact web cash related determining. Partially, listing age benefits internet financial reporting, but business size and auditor reputation have minimal impact.